Kajian Lebar Bangunan Pelimpah Tipe Lengkung Terhadap Elevasi Muka Banjir (Studi Kasus Waduk Tenayan) - Victory, Dany Elisa; Siswanto, Siswanto; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tenayan reservoir is a facility that included in the planning of infrastructure development Pekanbaru city government offices were built to meet the needs of the office of the raw water. Tenayan Reservoir drainage system is part of DAS system of Siak where natural systems there is a watershed Tenayan. In a study on the construction of the reservoir, spillway is an important study that is based on considerations of topography, hydrology and hydraulics. In this study the hydrological analysis to get the flood discharge design using Nakayau HSS. Further studies conducted by calculating the width of spillway flood search through the spillway (spillway) for various types of straight spillway with a width of 25 m and type of arch spillway with a variation of the radius of 12,5 m, 15 m, 20 m and 25 m in order to obtain flood level elevation for various the variations in the hydrological analysis result obtained Tenayan flood discharge design period of 20 years of rainfall data (1994-2013) for 100 year return period amounted to 182.063 m3 / second using Nakayasu HSS. By using the design flood discharge of the obtained spillway flood level elevation (crest elevation +20 m) for various types of overflow proportional to the width of 25m is +21.787 m and for overflow arch with a variation of the radius of 12,5m, 15m, 20m and 25 m respectively +21.399 m, +21.650 m, + 21,725m and + 21,750 m.Keyword : Reservoir, flood elevation level, spillway , HSS Nakayasu